ACCUMULATED EXPERIENCE IN TREATMENT OF COVID-19. OWN OBSERVATIONS AND WORLD DATA. LITERATURE REVIEW - Казанцев, Антон Николаевич; Черных, Константин Петрович; Хацимов, Кантемир Артурович; Багдавадзе, Годерзи Шотаевич (Medicine in Kuzbass, 2021)
The article is devoted to the accumulated Russian and world experience in the treatment of COVID-19 as of April 2021. The main methods of diagnosis and treatment are presented, as well as our conclusion on their relevance. The place of cardiovascular pathology in the spectrum of patients with new coronavirus infection is described. An increase in the number of emergency angiosurgical interventions was demonstrated in view of an increase in the number of arterial thrombosis and non-operated hemodynamically significant stenosis of the internal carotid arteries. The necessity of using a new glomus-sparing carotid endarterectomy (CEE) according to A.N. Kazantsev in the treatment of precerebral atherosclerosis. The main measures for the prevention of COVID-19 mediated complications after CEE are listed: 1) intravenous infusion of heparin at a dosage of 1000 IU per hour using an infusion pump after surgery; 2) acetylsalicylic acid 125 mg; 3) application of double drainage. Conclusions were made on a number of unresolved issues.
Keywords: COVID-19; novel coronavirus infection; emergency care; diagnosis of COVID-19; treatment of COVID-19; novel coronavirus; SARS-CoV-2; carotid endarterectomy; thrombosis; glomus-sparing carotid endarterectomy